2019
DOI: 10.1038/s41467-019-09547-6
|View full text |Cite
|
Sign up to set email alerts
|

Surface melt driven summer diurnal and winter multi-day stick-slip motion and till sedimentology

Abstract: Fluctuations in glacier motion are very common and are thought to be controlled by subglacial hydrology and till deformation. There are few instrumented studies that have monitored seasonal changes. We use the innovative Glacsweb subglacial in situ wireless probes, combined with dGPS and custom geophone data from an Icelandic soft-bedded temperate glacier, to show that there are two distinct seasonal styles of speed-up events. Relatively small diurnal events occur during the melt season, whilst during winter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 68 publications
0
40
1
Order By: Relevance
“…Recent instrumental and geophysical studies at Skálafellsjökull – an active temperate glacier with a similar landsystem signature to Fjallsjökull (cf. Evans and Orton, ; Chandler et al ., , c) – have shown that it has a very low water‐storage capacity and surface meltwater is rapidly transferred to the glacier bed via crevasses and moulins (Hart et al, , , ). A combination of this efficient englacial drainage system and high meltwater inputs results in saturated subglacial tills throughout the melt season at Skálafellsjökull (cf.…”
Section: Synthesis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent instrumental and geophysical studies at Skálafellsjökull – an active temperate glacier with a similar landsystem signature to Fjallsjökull (cf. Evans and Orton, ; Chandler et al ., , c) – have shown that it has a very low water‐storage capacity and surface meltwater is rapidly transferred to the glacier bed via crevasses and moulins (Hart et al, , , ). A combination of this efficient englacial drainage system and high meltwater inputs results in saturated subglacial tills throughout the melt season at Skálafellsjökull (cf.…”
Section: Synthesis and Discussionmentioning
confidence: 99%
“…A combination of this efficient englacial drainage system and high meltwater inputs results in saturated subglacial tills throughout the melt season at Skálafellsjökull (cf. Hart et al ., , ). The instrumental work has also recorded high water pressures during the entire melt season, which have been suggested to reflect an inefficient, distributed drainage system (Hart et al ., ; cf.…”
Section: Synthesis and Discussionmentioning
confidence: 99%
“…A combination of this efficient englacial drainage system and high meltwater inputs results in saturated subglacial tills throughout the melt season at Skálafellsjökull (cf. Hart et al, 2015Hart et al, , 2019b. The instrumental work has also recorded high water pressures during the entire melt season, which have been suggested to reflect an inefficient, distributed drainage system (Hart et al, 2019b;cf.…”
Section: Controls On Sub-annual Moraine Formationmentioning
confidence: 95%
“…Hart et al, 2015Hart et al, , 2019b. The instrumental work has also recorded high water pressures during the entire melt season, which have been suggested to reflect an inefficient, distributed drainage system (Hart et al, 2019b;cf. Schoof, 2010).…”
Section: Controls On Sub-annual Moraine Formationmentioning
confidence: 95%
See 1 more Smart Citation